MESIN PARKIR ELEKTRONIK SEBAGAI WUJUD DARI SMART CITY DI KOTA BANDUNG - Kireina, Nurani Fitri (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2017)
Electronic parking machine is a renewal by the city of Bandung in parking payments. Based on data show that eletronic parking engine began to be used in the city of Bandung since 2013. Basically the user of electronic parking machine is a form of use information and communication technology in government. It can support the city of Bandung as a smart city. In this case Rudolf Giffinger states that there are six characteristics to realize the smart city. In this case the electronic parking machine is expected to realize the city of Bandung as a smart city, it is strengthened by San Fransisco Municipal Transportation Agency (SMFTA) that the electronic parking engine is a smart parking system that can support the smart city. So need to do a qualitative research on electronic parking engine in Bandung city. The result of this study states that electronic parking engine has been installed in the city of Bandung since 2013. However, after about four years tested the machine is still not running.